Calibrating Canopy Reflectance Sensors to Predict Optimal Mid‐Season Nitrogen Rate for Cotton. Issue 1 (26th November 2012) - Oliveira, Luciane F.; Scharf, Peter C.; Vories, Earl D.; Drummond, Scott T.; Dunn, David; Stevens, W. Gene; Bronson, Kevin F.; Benson, N. Ray; Hubbard, Victoria C.; Jones, Andrea S.
Abstract : Inadequate N supply can limit yield of cotton ( Gossypium hirsutum L.), while too much N can cause excessive vegetative growth and delayed maturity. Reflectance sensors offer the potential to diagnose N need and to translate this diagnosis into a variable‐rate application of N in real time. Our objective was to calibrate canopy reflectance sensors to predict economically optimal N rate (EONR) in support of variable‐rate fertilization. Nitrogen rate experiments were conducted on three soils in 2006 and 2007. Reflectance was measured with three sensors (Crop Circle, GreenSeeker, and Cropscan) at three growth stages (early square, mid‐square, and early flower) and at three heights above the canopy (25, 50, and 100 cm). Economically optimal N rate ranged from 0 to 220 kg N ha −1, suggesting that the need to diagnose EONR is great. Relative reflectance for all three sensors was weakly related to EONR at the early square stage but was related more strongly at the mid‐square and early flower stages. Regression equations were not significantly different between mid‐square and early flower stages, suggesting that a single equation could be used to translate reflectance measurements to N rates over this period. Relationship to EONR was best for all sensors when placed 50 cm above the canopy. For these stages and height, all three sensors were similarly related to EONR ( r 2 = 0.59 to 0.62). These relationships could feasibly support successful variable‐rate N applications to cotton.